تقييم المخاطر في المصارف باستخدام ادوات الهندسة المالي مصرف جيهان أنموذجا للفترة )2012-2017 - Guldran Abdulrahim Azzez; Shakhawan babkr Hassan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The objective of this study is to identify the most important financial engineering tools used to assess risk in the bank by using some tools such as (index - Sherrod, liquidity indicators - capital adequacy indicators - operating indicators) for risk assessment in Cihan. High Risk Transactions This reduces the risk effects that the Bank may face in the future and the formulation of innovative solutions to financing problems. In order to achieve the objective of the study, the analytical approach was adopted to the data of the annual reports of Cihan during the study period. The study found that the Sherrod model could be used to assess credit risk when granting loans to economic projects. The results of the analysis indicate that Cihan Bank was granted loans from risk-weighted loans (category III) through the years 2013 to 2017 because the value of Z is greater than 20 and less than 25. In 2012, Cihan was granted loans from medium risk loans of (Class III), which amounted to 19.8%.